Characterization of thrombogenic, endothelial and inflammatory markers in supraventricular tachycardia: a study in patients with structurally normal hearts. (August 2014) - Schultz, Carlee D; Rangneker, Geetanjali; Lim, Han S; Fraudeau, Angelique; Young, Glenn; Roberts‐Thomson, Kurt; John, Bobby; Worthley, Matthew; Sanders, Prashanthan; Willoughby, Scott R
Summary: Patients with atrial fibrillation (AF) are at an increased risk of thromboembolism and stroke primarily from the development of thrombi within the left atrium. Pathological changes in blood constituents and atrial endothelial damage promote left atrial thrombus formation. It is not known whether factors predisposing to left atrial thrombus formation in AF are disease specific or also evident within the normal heart. The present study examined whether there are differences in platelet reactivity, endothelial function and inflammation in blood samples obtained from intracardiac and peripheral sites in subjects within structurally normal hearts. Sixteen patients with diagnosed left‐sided supraventricular tachycardia (SVT) undergoing a routine elective electrophysiological study and ablation were investigated. Blood samples were taken simultaneously from the femoral vein, right atrium and left atrium, immediately following trans‐septal puncture and prior to heparin bolus administration. Between peripheral and atrial sample sites, patients with SVT showed no change in platelet reactivity or aggregation (P‐selectin (CD62P) P  = 0.91; platelet‐derived soluble CD40 ligand P  = 0.9), thrombus formation (thrombin–antithrombin complex; P  = 0.55), endothelial function (von Willebrand factor P  = 0.75; asymmetric dimethylarginine (ADMA) P  = 0.97; nitric oxide P  = 0.61), or inflammation (vascular cell adhesion molecule‐1 P  = 0.59; intercellular adhesion molecule‐1 (ICAM‐1) P  = 0.69). However, SVT patients had lower ADMA and ICAM‐1 levels than AF patients. The present study demonstrates, for the first time, that SVT subjects with structurally normal hearts have consistent haemostatic function between atrial and peripheral sites. These results suggest that the atria of SVT patients do not contain predisposing thrombogenic, endothelial or inflammatory factors that promote and/or initiate thrombus formation.